A revision of the genus Rudolfina Roháček (Sphaeroceridae: Limosininae) - Paiero, Steven Mark; Marshall, Stephen A. (European Journal of Taxonomy, 2020)
The genus Rudolfina Roháček, 1987 is revised and redefined with the description of the following nine new species, all from the New World: R. bucki sp. nov. (Mexico), R. exuberata sp. nov. (widespread, from USA to Brazil), R. howdeni sp. nov. (Mexico), R. megepandria sp. nov. (Mexico), R. newtoni sp. nov. (Mexico), R. pauca sp. nov. (Guatemala, Mexico), R. pilosa sp. nov. (Mexico), R. remiforma sp. nov. (Mexico) and R. tumida sp. nov. (Mexico, USA). Rudolfina is compared to closely related genera in the Archiceroptera genus complex, which in turn is recognized as part of a large, mostly Neotropical clade including Robustagramma Marshall & Cui, 2005, Pterogramma Spuler, 1924, Aptilotella Duda, 1924, Bitheca Marshall, 1987, Bromeloecia Spuler, 1924 and Archiceroptera Papp, 1977.